Alternating tillage with conservation agricultural practices in intensive rice (Oryza sativa L.)-based cropping systems can improve soil health and increase crop and systems productivity in the Eastern Indo-Gangetic Plains - Hoque, Muhammad Arshadul; Gathala, Mahesh; Timsina, Jagadish; Ziauddin, A.T.M.; Hossain, Mosharraf; Krupnik, Timothy Joseph (Elsevier, 2025)
Available ariable land for agriculture in South Asia's Eastern Indo-Gangetic Plains (EIGP) is decreasing while the population and the demand for food is increasing. Despite this pressure to intensify land use, large tracts of land still remain fallow during the dry season. Making productive use of these lands is essential to increasing farm output while safeguarding food security. One potential part of the solution to this challenge lies in improved land management practices. Conservation agriculture with no or reduced tillage (CA), or alternating tillage where monsoon rice is established with full tillage and dry season crops with reduced or zero tillage (AT), can potentially facilitate improved crop establishment, increase yield, and improve soil health and the resilience of cropping systems. This study was undertaken to evaluate CA, AT and conventional tillage (CT) under double- or triple cropping sequences on loamy soil in a (sub) tropical environment in the EIGP northern Bangladesh. The experiment included six cropping systems (CS) over three consecutive years: CS1, Aman rice (Oryza sativa L.) – Boro or winter rice (Oryza sativa L.) (R-R); CS2, Aman rice – Wheat (Triticum aestivum L.) (R-W); CS3, Aman rice – Maize (Zea mays L.)(R-M); CS4, Aman rice - Mung bean (Vigna radiata L.) (R-M); CS5, Aman rice – Wheat – Mung bean (R-W-MB); and CS6, Aman rice – Maize – Mung bean (R-M-MB). In CS5 and CS6, mung bean replaced land fallowing after the predominant dry season crop. Maize, but not rice, yields were higher in AT or CA than CT. The R-W-MB and R-M systems had the highest system-level rice equivalent yield. Soil chemical properties, except SOM, total N, and Mn, in the 0–15 cm portion of the soil profile also differed significantly among the systems. Cropping systems had a significant effect on soil penetration resistance up to 30 cm soil depth. The buffering capacity of the soil under these treatments against diurnal temperature variation was also higher under CA followed by AT. These results suggest that AT with CA-based management practices can improve cropping systems level yields and soil properties. These practices can also be be adapted to rice-based farming systems where they can support improved land management and increase systems productivity and soil health. Long-term studies are required across soil types, climates, and socio-economic conditions to extrapolate findings to larger areas of the EGP.